Insights into Parasitic Fauna among Rescued Snake Species: A Study from Tamil Nadu, India - Tamileniyan, E.; Jeevitha, M.; Latchumikanthan, A.; Veeraselvam, M.; Velusamy, R.; Saravanan, M.; Kundave, V. R.; Ramkumar, P. K.; Senthilkumar, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study presents an investigation into parasitic fauna inhabiting various snake species from Tamil Nadu, India, focusing on ectoparasites and endoparasites. Over an 18-month period of study, sixteen snakes comprising Rat snakes, Indian cobra and Green vine snake were meticulously examined. Ectoparasite assessment unveiled ixodid ticks infestation, predominantly featuring Amblyomma gervaisi, alongside Amblyomma pattoni and Amblyomma cordiferum. Among the endoparasites identified, helminthic species included stronglyes, Oxyurid sp. and Pentastome sp., with instances of mixed infections observed. Protozoal infections were detected through blood and faecal analysis, with the detection of Haemoproteus sp., Hepatozoon sp., Cryptosporidium sp. and Eimeria sp. These findings emphasize the necessity for comprehensive monitoring of parasitic infections in snakes, not only for conservation endeavours but also for mitigating potential public health risks associated with zoonotic diseases and biological balance.